Analisis Kebutuhan Regulasi Terkait dengan Internet of Things [The Analysis of The Required Regulation of Internet of Things] - Diah Kusumawati; Bagus Winarko; Riva'atul Adaniah Wahab; Wirianto Pradono (Buletin Pos dan Telekomunikasi, 2017)
IoT Indonesia Forum predicted that IoT Indonesia market potential in 2020 reach about 35 billion dollars. This paper analyzes the IoT's regulatory requirements in Indonesia, which are safety standards, device standards, business implementation models, and IoT ecosystems, adapted to Indonesia's current conditions. The study uses qualitative approach. Primary data are obtained through in-depth interview and FGD and analyzed using three early stages of Regulatory Impact Analysis and Benefit, Opportunity, Cost, and Risk theory on each alternative. As the results, the parameters that needed to be regulated for each IoT issue include 1) Security standards: personal data protection, interoperability, data network security, and applications security; 2) Device standards: TKDN devices, system authentication, and device security, 3) Business model: spectrum utilization, and 4) Ecosystems: spectrum allocation. Recommendations that can be conveyed include the need for stakeholder cooperation to develop the IoT Indonesia Roadmap, increasing the amount of bandwidth in the existing frequency spectrum, reviewing existing equipment regulations according to the most widely used IoT technology in the world, what sector mapping is highly potential in Indonesia, privacy regulation and device security, reviewing TKDN policy requirements, and specific business models between domestic IoT producers for IoT use in the government sector*****Forum IoT Indonesia memprediksi potensi pasar IoT Indonesia tahun 2020 mencapai sekitar 35 miliar dolar. Tulisan ini menganalisis kebutuhan regulasi IoT di Indonesia yaitu standar keamanan, standar perangkat, model penyelenggaraan bisnis, serta ekosistem IoT untuk disesuaikan dengan kondisi Indonesia saat ini. Penelitian menggunakan pendekatan kualitatif. Data primer diperoleh melalui wawancara mendalam dan FGD serta dianalisis menggunakan RIA sampai tahap 3 dan teori BOCRterhadap masing-masing alternatif. Hasilnya, bentuk regulasi dapat berupa perubahan pada regulasi eksisting atau penyusunan regulasi spesifik IoT. Parameter yang dibutuhkan dalam regulasi IoT antara lain alokasi dan pemanfaatan spektrum, TKDN perangkat, protokol komunikasi, sistem otentifikasi dan keamanan perangkat, standar power, perlindungan data pribadi, keamanan data, interoperabilitas, keamanan transmisi data, enkripsi data, keamanan jaringan, keamanan konektivitas, dan keamanan pada aplikasi IoT. Rekomendasi yang dapat disampaikan yaitu perlu kerjasama antarstakeholder untuk menyusun Roadmap IoT Indonesia, penambahan jumlah bandwidth pada spektrum frekuensi eksisting, mengkaji regulasi eksisting perangkat sesuai teknologi IoT yang paling banyak digunakan di dunia, pemetaan sektor apa yang sangat berpotensi di Indonesia, regulasi privasi dan keamanan perangkat, mengkaji kebijakan persyaratan TKDN, pengoptimalan inkubator riset dalam negeri untuk produksi PCB, adanya sertifikasi keahlian, danmodel bisnis khusus antara produsen IoT dalam negeri untuk penggunaan IoT di sektor pemerintah.